Pathological phenotypes of body composition in patients with rheumatic diseases - A. O. Sorokina; N. V. Demin; O. V. Dobrovolskaya; O. A. Nikitinskaya; N. V. Toroptsova; A. Yu. Feklistov (Научно-практическая ревматология)
Aim – to identify the frequency of isolated and combined pathological phenotypes of body composition in women with rheumatic diseases and to determine the factors associated with the sarcopenic phenotype.Materials and methods. 255 women (median age 60 [54; 64] years) were included in the study: 114 patients with rheumatoid arthritis (RA), 46 – with systemic sclerosis (SSc), 56 – with osteoarthritis (OA), and 39 persons without rheumatic diseases (control). Questionnaires, anthropometric measurements, double-energy X-ray absorptiometry of the whole body, lumbar spine and proximal femur were performed. The assessment of the factors associated with the sarcopenic phenotype was carried out using a univariate regression analysis.Results. The frequency of isolated and combined pathological phenotypes in women with SSc was 34.8% and 52.2%, with RA – 51.8% and 38.6%, with OA – 71.4% and 10.7%, respectively. The sarcopenic phenotype was more often determined in patients with SSc (43.5%) and RA (29.8%) compared with women with OA (1.8%) (p<0.001). The factors associated with the sarcopenic phenotype were BMI><25 kg/m2 (OR=7.89 [95% CI: 3.90–15.96]; p><0.001), glucocorticoids (GC) intake (OR=2.50 [95% CI: 1.32–4.73]; p=0.005) and cumulative GC dose (OR=1.04 [95% CI: 1.01–1.07]; p=0.008), presence of osteoporosis (OP) (OR=4.31 [95% CI: 2.33–7.97]; p><0.001), leukocytosis more than 9.0×109 /l (OR=4.08 [95% CI: 1.38–12.10]; p=0.011), total protein less than 65 g/l (OR=1.11 [95% CI: 1.02–1.19]; p=0.019) and calcium intake less than 500 mg/day (OR=2.78 [95% CI: 1.39–5.53]; p=0.004). Conclusion. The study demonstrated a significant frequency of pathological phenotypes of body composition in women with rheumatic diseases, while combined phenotypes were more common in patients with SSc and RA compared with patients with OA. The probability of sarcopenic phenotype increased with BMI><25 kg/m2 , GC using, the presence of OP and insufficiency of calcium intake. Key words: rheumatic diseases, body composition phenotypes, sarcopenia, osteoporosis, osteosarcopenia, overfat, rheumatoid arthritis, systemic scleroderma, osteoarthritis, risk factors>˂ 0.001). The factors associated with the sarcopenic phenotype were BMI<25 kg/m2 (OR=7.89 [95% CI: 3.90–15.96];>˂ 25 kg/m2 (OR=7.89 [95% CI: 3.90–15.96]; p<0.001), glucocorticoids (GC) intake (OR=2.50 [95% CI: 1.32–4.73]; p=0.005) and cumulative GC dose (OR=1.04 [95% CI: 1.01–1.07]; p=0.008), presence of osteoporosis (OP) (OR=4.31 [95% CI: 2.33–7.97]; p><0.001), leukocytosis more than 9.0×109 /l (OR=4.08 [95% CI: 1.38–12.10]; p=0.011), total protein less than 65 g/l (OR=1.11 [95% CI: 1.02–1.19]; p=0.019) and calcium intake less than 500 mg/day (OR=2.78 [95% CI: 1.39–5.53]; p=0.004). Conclusion. The study demonstrated a significant frequency of pathological phenotypes of body composition in women with rheumatic diseases, while combined phenotypes were more common in patients with SSc and RA compared with patients with OA. The probability of sarcopenic phenotype increased with BMI><25 kg/m2 , GC using, the presence of OP and insufficiency of calcium intake. Key words: rheumatic diseases, body composition phenotypes, sarcopenia, osteoporosis, osteosarcopenia, overfat, rheumatoid arthritis, systemic scleroderma, osteoarthritis, risk factors>˂ 0.001), glucocorticoids (GC) intake (OR=2.50 [95% CI: 1.32–4.73]; p=0.005) and cumulative GC dose (OR=1.04 [95% CI: 1.01–1.07]; p=0.008), presence of osteoporosis (OP) (OR=4.31 [95% CI: 2.33–7.97]; p<0.001), leukocytosis more than 9.0×109 /l (OR=4.08 [95% CI: 1.38–12.10]; p=0.011), total protein less than 65 g/l (OR=1.11 [95% CI: 1.02–1.19]; p=0.019) and calcium intake less than 500 mg/day (OR=2.78 [95% CI: 1.39–5.53]; p=0.004).>˂ 0.001), leukocytosis more than 9.0×109 /l (OR=4.08 [95% CI: 1.38–12.10]; p=0.011), total protein less than 65 g/l (OR=1.11 [95% CI: 1.02–1.19]; p=0.019) and calcium intake less than 500 mg/day (OR=2.78 [95% CI: 1.39–5.53]; p=0.004).Conclusion. The study demonstrated a significant frequency of pathological phenotypes of body composition in women with rheumatic diseases, while combined phenotypes were more common in patients with SSc and RA compared with patients with OA. The probability of sarcopenic phenotype increased with BMI<25 kg/m2 , GC using, the presence of OP and insufficiency of calcium intake. Key words: rheumatic diseases, body composition phenotypes, sarcopenia, osteoporosis, osteosarcopenia, overfat, rheumatoid arthritis, systemic scleroderma, osteoarthritis, risk factors>˂ 25 kg/m2, GC using, the presence of OP and insufficiency of calcium intake.